2016
DOI: 10.3892/ol.2016.5517
|View full text |Cite
|
Sign up to set email alerts
|

Trametes robiniophila may induce apoptosis and inhibit MMPs expression in the human gastric carcinoma cell line MKN-45

Abstract: Abstract. Gastric carcinoma (GC) is one of the most common malignant tumors and is mainly treated by invasive surgeries. The present study aimed to investigate the treatment potential of Trametes robiniophila on GC using the human GC cell line MKN-45. Cells were incubated with Trametes robiniophila at a concentration of 0, 5 and 10 mg/ml for 24 h. The apoptosis of the cell line was examined with acridine orange/ethidium bromide staining and flow cytometry. The expression of B-cell lymphoma (Bcl)-2, Fas, caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Ji et al showed that TR induces apoptosis in the human GC MKN-45 cell line through mitochondrial and the member receptor signaling pathways. TR, by reducing the expression of MMP-2 and MMP-9, inhibits the ability of GC cells to metastasize [ 179 ]. TR by reducing the expression of PI3K inhibits the expression of AKT, p-AKT, PTEN, and p-PTEN.…”
Section: Current Treatment Strategies For Emt Inhibition In Gastrimentioning
confidence: 99%
See 1 more Smart Citation
“…Ji et al showed that TR induces apoptosis in the human GC MKN-45 cell line through mitochondrial and the member receptor signaling pathways. TR, by reducing the expression of MMP-2 and MMP-9, inhibits the ability of GC cells to metastasize [ 179 ]. TR by reducing the expression of PI3K inhibits the expression of AKT, p-AKT, PTEN, and p-PTEN.…”
Section: Current Treatment Strategies For Emt Inhibition In Gastrimentioning
confidence: 99%
“…A decrease in AKT phosphorylation leads to a decrease in the expression of pro-caspase-9 and Bcl-2. TR by modulating the PI3K/AKT pathway by inhibiting PI3K expression induces apoptosis of human GC cells [ 179 ]. Zhenga et al demonstrated that TR polysaccharides inhibit invasion and migration of hepatocellular carcinoma cells by blocking AEG-1 signaling and restoring EMT in MHCC97-H cells [ 180 ].…”
Section: Current Treatment Strategies For Emt Inhibition In Gastrimentioning
confidence: 99%
“…13 According to the records of TCM, Huaier is usually used as an anti-inflammatory. 14 As pointed out in recent explorations, Huaier extract could play an anti-tumor role in a variety of malignant tumors, such as gastric cancer, lung cancer, osteosarcoma and breast cancer. [15][16][17][18] Meanwhile, Huaier could also strengthen the organic immunity by up-regulating the activity of natural killer cells and T cell subsets.…”
Section: Introductionmentioning
confidence: 97%
“…However, the anticancer effect of proteoglycan is less effective than that of the Huaier extract (Lee et al 2007; Yang et al 2017). Huaier has been con rmed to be effective against various cancers through some types of mechanisms, such as inhibition of tumor-induced angiogenesis, inhibition of cell growth, induction of apoptosis, and epithelial-mesenchymal transition (Ji et al 2017;Pan et al 2019). However, to the best of our knowledge, research on the effects of Huaier on OS cells is scarce.…”
mentioning
confidence: 99%
“…8 and clone formation assays to show that Huaier can reduce the viability and inhibit the proliferation of OS cells. Previous studies have shown that numerous anticancer medicines can arrest the cell cycle in the G0/G1, S, and G2/M phases(Lee et al 2007).…”
mentioning
confidence: 99%